The line upon a wind The greatest war fought at sea under sail : 1793-1815 - Mostert, Noel (Vintage Books, 2008)
In February 1793, France declared war on Britain and Holland. The Revolutionary and Napoleonic Wars that raged for the next twenty-two years saw European powers manoeuvering for mercantile and political advantage in a complex and ever-changing web of alliances and coalitions. By 1815, the world was a different place; age-old certainties were shattered, established dynasties and kingdoms overthrown, the United States emerged as a world power, and a new age was dawning. This was to be the longest, hardest and cruelest war ever fought at sea, on a scale comparable only with the Second World War. Methods of battle under sail, little changed for centuries, would be forced to adapt at an unprecedented pace that brought with it the fearsome power of rockets, torpedoes and submarines. The Line Upon a Wind is also the story of the daily lives of the sailors on board the fighting ships, the blood and guts ferocity of engagement in an age of gentility, the struggle of ships' surgeons to repair broken bodies and the daily struggle to keep the men fed and free of disease. It is a story of ordinary men and extraordinary bravery.